Right and freedom to participate the religious activities: transcending challenges among Thai Buddhists and Muslims in the southern border provinces - Makeng, Muhummudrapee; Manmanah, Direak; Tuanbula, Kholaf (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
This article presents transcending challenges of the right and freedom to participate the religious activities via a group of working people who need to interact among different congregations both Thai Buddhists and Muslims in the southern border provinces. This study considers the right to freedom of religion, follow the principles, commandments, perform religious rituals, and religious activities involving groups of people interacting with each other. According to the research study, it was found that the working people who needed to interact between the religious communities had relatively little knowledge and understanding of the freedom to participate in religious activities among Thai Buddhists and Muslims. In addition, they have an incomprehensible understanding of religious principles. This is due to the following significant factors: 1) the basic knowledge of religion, 2) growing up in a monocultural society. and 3) transcending challenges in cultural differences learning.